DESIGN THINKING IN THE CONTEXT OF PEDAGOGY - Krumina, Aira Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The concept of “design thinking” is thought to originate at late 60’s of the last century when the first books in this regard were published. Latest in 1987, Professor P. G. Rowe, (University of Harvard) describes design thinking as a process and a method which can be used in various disciplines, including in education. Thus the field of design and architecture began; nowadays design thinking has become an effective learning strategy. The method is based on not declining anything right off the bat but rather go in-depth, test, analyze, look at things multiple (at least two) times and look at them from different angles. It is believed that each of us has design thinking, we only need to activate it, “set it free”, and the faster we do it, the better; that is exactly why design thinking should be started at an early age, during school years, not only when in college or university.Design thinking as a thought process is one of the future skills which will be needed in 21st century’s wide variety of fields – design, economics, construction, architecture, engineering, technology and, of course, in education. Different sources of literature point out a different number of designs thinking stage (thinking “steps”) count: from three to seven or eight that can be represented both as a linear process and as a single complex system in which interconnection of stages/ steps is seen. In the study course of pedagogy students of different study programs and study courses (physiotherapists, audiologists, orthotics-prosthetists, nutrition specialists, social workers) tested and evaluated some of the basic principles of design thinking, such as empathy, creativity, collaboration, responsibility and interdisciplinary approach. Also students adapted and improved pedagogical strategies for developing design thinking in the practice. Those strategies were: generation ideas, designing and presentation of possible solutions, solving problems, creation prototypes, drawing empathy maps. The first results of approbated design thinking principles and methods are analyzed in this article.